Pengaruh Senam Lansia terhadap Tingkat Depresi pada Lansia di Panti Jompo - Bachtiar Safarudin; Rizqi Fitriyah Makmur; Sendy Glaudia Dede Tule; Herlinda, Herlinda; Nina Maulida (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Indonesia is currently entering the aging population phase, namely the proportion of the elderly population (lansi) is increasing. In Indonesia, around 12 percent of the population, or 29 million people, are classified as elderly. Mental health problems, especially depression, are a serious concern, with 70% of the elderly experiencing symptoms of depression. This study aims to determine the Effect of Elderly Gymnastics on Depression Levels in the Elderly in Nursing Homes. Elderly gymnastics is a light sport that is easy to do and not burdensome, which can be applied to the elderly which is useful for reducing and preventing depression in the elderly. The method used uses a systematic literature review approach by following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. By searching for literature in several databases, namely PubMed, Scopus, Google Scholar, and ScienceDirect, focusing on articles published between 2020 and 2025. The results of the study show that the Effect of Elderly Gymnastics on Depression Levels in the Elderly in Nursing Homes can improve the quality of life of the elderly, reduce depression levels, and encourage them to remain physically and socially active..